KUALITAS PELAYANAN KESEHATAN UNIT RAWAT JALAN TERHADAP KEPUASAN PASIEN DI PUSKESMAS BIAU KABUPATEN BUOL - S.B. Sihira, Serly; Alam, Samsul; Muliati, Sri (STISIPOL Mujahidin Buol, 2022)
Puskesmas is the leading functional, administrative and physical unit that carries out various main health businesses in an area that directly provide services to the community (Wardanengsih et al., 2019) Quality health services are health services that can satisfy every service user health in accordance with the level of satisfaction of the average population and its implementation in accordance with the existing code of ethics and professional service standards. Dansky said that customer or patient satisfaction is the basic principle of quality quality management (Machmud, 2008). The purpose of this study was to determine the level of outpatient patient satisfaction on patient satisfaction at the Biau Health Center, Buol District. The type of research used is descriptive. Conclusion The quality of outpatient unit health services for patient satisfaction at the Biau Health Center is not optimal because in terms of ability there are still some nurses who still need assistance in terms of taking action besides that there are still some facilities and infrastructure that are still lacking such as infusion poles and infusion tubes. the supply of medical devices and drug stocks are often empty, resulting in a large number of patients who have to be referred to advanced hospitals. One of the most fundamental elements of quality service management is continuous employee development through education and training.